Handbook of food process modeling and statistical quality control with extensive MATLAB applications - Özilgen, Mustafa (CRC Press, 2011)
"Presenting mathematical prerequisites in summary tables, this book explains fundamental techniques of mathematical modeling processes essential to the food industry. The author focuses on providing an in-depth understanding of modeling techniques, rather than the finer mathematical points. Topics covered include modeling of transport phenomena, kinetic processes, and food engineering operations. The book also discusses statistical process analysis and quality control. It includes examples from almost every conceivable food process, most of which are based on real data given in the many references. Each example is followed by a clear, step- by-step worked solution"-- Provided by publisher.
Rev. ed. of: Food process modeling and statistical quality control. 1998.
Keywords: Food industry and trade -- Production control -- Mathematical models.; Food industry and trade -- Quality control -- Statistical methods.; elektronické knihy; electronic books